2020
DOI: 10.3389/fnagi.2020.610626
|View full text |Cite
|
Sign up to set email alerts
|

Declining Trends of Heart Rate Variability According to Aging in Healthy Asian Adults

Abstract: Heart rate variability (HRV) indices correlate with aging and are related to the autonomic nervous system. However, the trend of HRV with age has not been explored for the Asian population. Therefore, we proposed a linear regression model of HRV indices that decreased with aging in healthy Asian adults. HRV parameters [High frequency (HF), Low frequency (LF), Very low frequency (VLF), Total power (TP), HRV triangular index (HRV-index), Standard deviation of the normal-to-normal interval (SDNN), and Proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
(71 reference statements)
8
16
0
2
Order By: Relevance
“…In addition, the results of the present study demonstrated that age and nursing seniority were significantly and negatively correlated with daytime dysfunction, TP and HF. This finding confirmed that of several studies that indicated that age and HRV correlated negatively [ 41 , 42 ]. The literature reveals that several factors influence HRV [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, the results of the present study demonstrated that age and nursing seniority were significantly and negatively correlated with daytime dysfunction, TP and HF. This finding confirmed that of several studies that indicated that age and HRV correlated negatively [ 41 , 42 ]. The literature reveals that several factors influence HRV [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finding confirmed that of several studies that indicated that age and HRV correlated negatively [ 41 , 42 ]. The literature reveals that several factors influence HRV [ 41 ]. One study pointed out that HRV analysis is affected by many factors, including caffeine, age, disease, BMI, day and night festivals, heart rate, acute psychological stress, etc.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The convergence of low and high frequencies of resting heart rate variability onto latent vascular factor 3 does not necessarily rule out frequency-specific effects on cognition, or frequency-specific effects of task-based heart rate variability modulation/reactivity (Laborde et al, 2018; Lui et al, 2022). Latent vascular factor 3 associated negatively with age, consistent with previous studies on heart rate variability (Choi et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The low HF power of delirium patients may be due to their tendency to be older than patients who do not experience delirium. Aged people showed lower HF power [ 22 , 23 ]. Due to the small sample size of this study, it was not possible to analyze the effects of age.…”
Section: Discussionmentioning
confidence: 99%